SISTEM INFORMASI PEMESANAN PAPAN BUNGA PADA VICTORIA FLORIST MEDAN BERBASIS WEB - Sedarmin Sebayang; Bersama Sinuraya (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2018)
Flower board is one tool to express the good feeling of gratitude, sorrow. Diera development of information technology today it turns out there are still many upper and middle class companies do not follow the development of technology, where technology is increasingly rapid in the current era of globalization. All this time, flower board ordering at CV Victoria Florist has not been able to develop, either marketing or ordering each month because consumers need fast service and there is no need to choose a flower board at the location of the order. therefore to anticipate as well as to cope with service and ordering problems, we need a system that is able to overcome these problems to make consumers feel comfortable and timely in ordering flower boards.